The arrest of indigenous people and judicial inspection (Revista do Tribunal Regional Federal da 3ª Região, 2011)
Both the original constituent power, the infra-constitutional legislature and the Federal State wanted to give differentiated treatment to protect indigenous communities, due to the very life they lead, that is, more communal than individual, with their housing, hunting, planting and even their imprisonment, when they have to be punished criminally. For imprisonment in a village, the State-Judge must ensure, by means of a judicial inspection, duly materialized in a site examination report and photographs, that the accused and/or convicted person lives there in an indigenous community, preserving the traditions of their ancestors, according to their own cultural patterns, social institutions and systems. We emphasize that this benefit should apply both to indigenous people who live in villages and to those who have been influenced in some way by the culture of non-indigenous society, i.e. white people, as long as they can prove that they are recognized by the indigenous community and that their segregation from it affects them.
Keywords: indigenous; prison; judicial inspection